Analisis Resiko Keuangan Dengan Menggunakan Metode Altman Z-Score (Studi Pada PT. Bank Rakyat Indonesia. Tbk Tahun 2011-2013) - Kuswantoro, Noffi, Drs. Ma'ruf, MM (2016)
The purpose of this study was to determine the level of bankruptcy PT. Bank Rakyat Indonesia.Tbk Year 2011-2013 using the Altman Z-Score. In this study population used in this research is financial statements (balance sheet and income statement) PT.Bank Rakyat Indonesia Tbk. While the sample is in the form of an income statement, balance sheet at PT.Bank Rakyat Indonesia Tbk. 2011-2013. Based on the results of the analysis of the results obtained in the Altman Z-Score Y PT.Bank financial performance in 2011-2013 with a Z-Score of the year 2011 = 0.4988, 2012 = 0.5240, 2013 = 0.5500. Based on the categories used in the Altman Z-Score that PT.Bank Rakyat Indonesia in the category of less than 1.81, which means that the company is experiencing financial difficulties were enormous. Thus, in relation to that category predicted PT.Bank Rakyat Indonesia Tbk. There is likely to be experiencing potential bankruptcy at any time.